Development of CRISPR-Cas9-mediated site-directed mutagenesis of ECE1 gene (candidalysin) in Candida albicans - Engku Nasrullah Satiman, Engku Anis Fariha; Kaderi, Mohd Arifin; Ramzi, Ahmad Bazli; Arzmi, Mohd Hafiz (2020)
CRISPR-Cas9 has been extensively used in microbial editing considering its specificity and versatility. Cumbersome editing in C. albicans due to its aberrant chromosomal ploidy and lock of meiosis can be potentially solved using CRISPR-Cas9. In this study, the third KR (lysine-arginine) motif on the ECEI gene that encodes for candidalysin in C.olbicans is targeted. The third KR motif (AAGAGA) is substituted into KA motif (AAGGCA) through transformation of CRISPR-Cas9 ribonucleoprotein (RNP) complex, ssDNA and pYM70 that confers hygromycin B resistance into competent cells of C. albicans using electroporation. The cleaving efficiency of the designed sgRNA is tested using in vitro nuclease assay against several concentrations of RNP prior transformation. The RNP complex that formed through co-incubation of sgRNA and purified Cas9 induced double-stranded break to the nearest protospacer adjacent motif to the third KR site. The DNA break is repaired by co-transformed ssDNA that contains KA motif at the third KR nucleotides flanked by 90 bp homologous arms via homologous recombination. The transformants were grown on YPD infused hygromycin B (600 µg/ml) for growth and selection. Mutation in successfully grown colonies will be verified through sequencing. The designed sgRNA shows in vitro efficient cutting at RNP concentrations of 15 nM, 20 nM and 25 nM. CRISPR-Cas9 is expected to direct correct substitution of bases that encodes for alanine at the third KR motif of the ECE1 gene. This study shall contribute to new approaches of gene editing and site-directed mutagenesis in C. albicons as well as in other in vitro and in vivo models.